Business Strategy To Increase Competitiveness and Profitability of Premios Dessert (The Indonesian Journal of Business Administration, 2021)
Nowadays, culinary industry was growing up, online system also was very reliable in terms of supporting the business such as promoting, marketing, selling, and delivering the food. In this situation,the owner of Premios Dessert does not want to miss the opportunity. They run the business of dessert in one of apartment located at North Jakarta which the business classified as home industry scale. After running for 3 years, several strategies have been applied to improve the process of production, increase customer satisfaction, and increase the revenue as well. However, the number of monthly selling stuck in average of 150 packs.Some improvement on business strategy must be in placed to overcome the low growth of selling number. In order to formulate the improvement strategy, internal analysis and external analysis are conducted as well as gap analysis then identifying the root cause. The methodology that used for analysis in this research was based on quantitative and qualitative data that gathered from literature study, business owner, internet searching, market place and also survey from customer. The aspect from internal that analyzed to discover the competitive advantage of Premios Dessert are resources, capabilities, core competencies and value chain. The aspect from external that analyzed to identify the existing opportunities and threats are general environment consist of Demographic, PEST and Sustainable Physical Environment; Industry environment consist of Porter’s Five Forces; and Competitor environment analysis. The aspect that analyzed to identify the gap are customer analysis and SWOT analysis. In identifying the root cause, 5 Why method is used and the result is current financial capacitiy only afford for current business scale.By having a comprehensive analysis and to address the issue, there are 7 strategies are developed by using TOWS Matrix. The strategies then divided into 3 main strategies which are increase competitiveness by upgrading the financial resources, improve the internal management and improve the marketing strategy. The implementation of these strategies will be divided into short term and medium-long term implementation. Keywords: Dessert, business strategy, monthly selling